Peran Masjid Sebagai Media Dakwah Di Stiba Ar Raayah Sukabumi - Tatang Hidayat; Muhammad Khairul Anam; Istianah Istianah (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
The mosque is the most significant center of worship, especially when it comes to issues of community development and education. This study aims to analyze the role of the mosque as a medium of da'wah at STIBA Ar Raayah. This research collects data from primary and secondary sources using a qualitative approach and descriptive method. Data collection techniques with interviews, observation and documentation. Data analysis technique with data interpretation. Based on the results of the study, the role of the STIBA Ar Raayah mosque is in accordance with the role of the mosque in the era of the Prophet Muhammad SAW, namely as a place of worship, an educational center, a social and cultural place, a center for da'wah activities, and a community role. The STIBA Ar Raayah mosque has played a role and functioned as the role of the mosque in the days of the Prophet Muhammad SAW and his companions. The purpose of building a mosque at STIBA Ar-Raayah is to become a medium for students on campus to preach and train themselves before going into the community.